Pola Konsumsi Natrium dan Lemak sebagai Faktor Risiko Terjadinya Penyakit Hipertensi di Wilayah Kerja Puskesmas Kandangan Kecamatan Kandangan Kabupaten Hulu Sungai Selatan - Yuliana Salman; Rosihan Anwar; Ahmad Muhaimin; STIKES Husada Borneo; Poltekes Banjarbaru; Alumni STIKES Husada Borneo (Jurnal Kesehatan Indonesia, 2015)
Hypertension is still a major problem in the world. According to the WHO, hypertension is the number 1 cause of death in the world. The prevalence of people with hypertension in Indonesia reaches 31,7%, while prevalence of people with hypertension in South Borneo reaches 39,6% and in the District of Hulu Sungai Selatan as much as 12.99% . The high hypertension patients in the district Hulu Sungai Selatan due to an unhealthy lifestyle is also encouraged by the consumption pattern of local people, such as food named Ketupat Kandangan, with the sauce or marinade containing moderately high cholesterol. This study aims to determine the pattern of sodium and fat consumption as a factor in the occurrence of hypertension in health care center Kandangan District of Hulu Sungai Selatan. This study uses observations with case control design. The study sample group of 84 respondents, 42 respondents with hypertension (cases) and 42 respondents did not suffer from hypertension (control). Results of statistical tests using chi-square shows, the pattern of consumption of sodium obtained p = 0,000 and fat consumption patterns obtained value of p = 0.016 which means that there is a relationship of sodium and fat consumption patterns with the occurrence of hypertension.